Application of Analytical Hierarchy Process in Functional Position Credit Point Assessment - Yudi Wiharto; Mufti Mufti; Subandi Subandi; Anita Diana (International Journal of Computer Technology and Science, 2025)
Credit score evaluation for functional positions is a critical component in the career development of employees at the Financial Supervisory Agency (BPK) in Jakarta. However, this evaluation process often encounters challenges related to objectivity, consistency, and transparency due to the combination of qualitative and quantitative criteria. This study aims to apply the Analytical Hierarchy Process (AHP) as a decision support tool in the credit score assessment system. AHP is chosen for its ability to break down complex problems into a hierarchical structure and to assign priority weights through pairwise comparisons among criteria. This method is used to determine the priority weights of each evaluation component, including both main and supporting elements, leading to more structured and accountable decisions. The findings indicate that the implementation of AHP enhances the accuracy and objectivity of the credit score evaluation process for functional positions at BPK. Therefore, this approach can serve as the foundation for developing a more transparent and efficient technology-based assessment system.